Fuelwood value chain in Northern Nigeria: Economic, environment, and social sustainability concerns - Ali, Bulama; Saadun, Norzanalia; Kamarudin, Norizah; Alias, Mohamad Azani; Mohd Nawi, Nolila; Azhar, Badrul (Multidisciplinary Digital Publishing Institute, 2023)
The increased fuelwood demand and commercialization activities in Nigeria over the years have incurred various sustainability issues and concerns along the fuelwood value chain. This study employed value chain analysis to examine the sustainability of the fuelwood value chain in Yobe, Nigeria, in relation to economic, environmental, and social aspects. From the analysis, it was found that fuelwood business activities were conducted by registered licensed actors (formally) and informally by non-licensed actors who do not register with the government agency that controls forest-related activities. Profit was not equally distributed along the value chain, whereby 65% of the total profits were reaped by the transporters. Natural forests were the main source of fuelwood, with 18 tree species being preferred and commonly traded by both formal and informal chain actors. Women’s participation in the formal fuelwood value chain was limited and mainly concentrated in the informal chain. The findings of this study can inform policymakers to enhance the sustainability of fuelwood production and trade along the value chain, especially in terms of profit sharing, exploitation of forest resources, and gender equality.